Sintering of amorphous calcium phosphate to near-full density by uniaxial compaction at room temperature. Issue 13 (October 2022) - Rubenis, Kristaps; Zemjane, Signe; Vecstaudza, Jana; Lazdovica, Kristine; Bitenieks, Juris; Wiecinski, Piotr; Indurkar, Abhishek; Locs, Janis
Abstract: Amorphous calcium phosphate is a metastable phase with excellent biocompatibility and resorbability. Despite these characteristics, its use is currently limited to the powder and coating forms; only moderate success has been achieved in its densification, which has prevented its use in the bulk form. Here, we show that amorphous calcium phosphate can be sintered to near full density by simple uniaxial die pressing at 1250–1500 MPa at room temperature. The relative densities of the samples that were compacted at 1250 and 1500 MPa exceeded 95 %. Their specific surface area was more than 1000 times smaller than that of the starting powder and their Vickers hardness exceeded 1.90 GPa. The microstructures of the samples consisted of a grain-like structure with grain sizes below 100 nm. These results could inspire new applications for amorphous calcium phosphate in the form of bulk ceramics. Highlights: Amorphous calcium phosphate can be sintered by uniaxial die pressing at room temperature. Relative density of the samples obtained at 1250–1500 MPa exceeded 95 %. Vickers hardness of near-fully dense (relative density >95 %) amorphous calcium phosphate ceramics exceeded 1.9 GPa.